Study on Optimization of Carboxymethylation of Chitosan Obtained from Squilla Chitin - Bedekar, A.N.; Pise, A.C.; Thatte, C.S.; Rathnam, M.V. (Asian Journal of Chemistry, 2010)
The physico-chemical characteristics of chitin, chitosan and their derivatives differ with crustacean species and preparation methods. The relationship between process conditions and characteristics of chitin and chitosan products are monitored to achieve uniformity and proper product quality control. Chitin, chitosan and its derivatives are mainly obtained from prawns and crab. In the present study alternative source squilla, a by-catch of Indian ocean fisheries is studied for preparation of chitin, chitosan and its water soluble derivative carboxymethyl-chitosan having unique chemical, physical and biological properties. With green chemistry approach further work was carried out to minimize the chemicals going to effluent. The carboxymethylation of chitosan was optimized by variation in solvent, mole ratio of NaOH to Chloroacetic acid and reaction parameters like temperature and time. Carboxymethylchitosan sample prepared was checked by gel permeation chromatography.